2014
DOI: 10.1002/etc.2616
|View full text |Cite
|
Sign up to set email alerts
|

Determination of nanosilver dissolution kinetics and toxicity in an environmentally relevant aqueous medium

Abstract: Assessing the dissolution of silver nanoparticles (AgNPs) in laboratory test media and in the aquatic environment is critical for determining toxicity. In the present study, the ion-release kinetics for 20-nm, 50-nm, and 80-nm AgNPs in environmentally relevant freshwaters with different electrical conductivity values (30 µS/cm, 150 µS/cm) were examined and related to the associated impact on Daphnia magna. The acute toxicity of the AgNP suspensions to D. magna was assessed after 0 d and 7 d of interaction time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…The higher toxicity of Ag NPs to algal cells was observed in acidic media (Oukarroum et al, 2014) and media with high ionic strength (Chambers et al, 2014), owing to the increased release of silver ions. However, the inverse phenomenon was reported in several studies where Ag NPs demonstrated decreased toxicity in media with higher ionic strength (Gao et al, 2009;Harmon et al, 2014). Mitigated bactericidal effects of ZnO NPs (Li et al, 2013) and TiO 2 NPs (Lin et al, 2014) were also observed in media with high pH or ionic strength.…”
Section: Introductionmentioning
confidence: 77%
“…The higher toxicity of Ag NPs to algal cells was observed in acidic media (Oukarroum et al, 2014) and media with high ionic strength (Chambers et al, 2014), owing to the increased release of silver ions. However, the inverse phenomenon was reported in several studies where Ag NPs demonstrated decreased toxicity in media with higher ionic strength (Gao et al, 2009;Harmon et al, 2014). Mitigated bactericidal effects of ZnO NPs (Li et al, 2013) and TiO 2 NPs (Lin et al, 2014) were also observed in media with high pH or ionic strength.…”
Section: Introductionmentioning
confidence: 77%
“…Test media properties such as pH (El Badawy et al, 2010) and ionic strength (Harmon et al, 2014;Tejamaya et al, 2012) impact stability. Therefore, while standardized tests typically allow flexibility in selecting from multiple test media types ranging from very soft water to very hard water (e.g., OECD, 2012; USEPA, 2002a), such flexibility is problematic for acquiring consistent (repeatable) results from ENM hazard testing (Petersen et al, 2015).…”
Section: Test Media Modificationsmentioning
confidence: 99%
“…Similarly, Ma et al (2012) diluted EPA-MHRW fourfold and 100-fold in TiO 2 tests with Daphnia magna and Japanese Medaka, respectively, and pretested both species in the modified media to confirm organism health. Decisions to reduce the ionic strength of testing media for particle stability must also consider the environmental relevance and test organism health (Harmon et al, 2014) and comparison to historical databases for a test method (Petersen et al, 2015). If stability was improved in the modified media, that media is acceptable for use in bioassays.…”
Section: Test Media Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present protocol utilizes the methods outlined in ISO 2000, , and Taurozzi 2013 for pre-dispersion of NP powder for stock generation. Aqueous NP stock generation, mixing, dilutions, and media spiking methods/ recommendations are leveraged from ISO 2000, Jiang et al 2009, Kennedy 2009, Kennedy 2010, Romer 2011, Taurozzi 2011, Kennedy 2012, Handy et al 2012, Tejamaya et al 2012, Harmon et al 2014.…”
Section: Introductionmentioning
confidence: 99%